(untitled) (Research, Society and Development, 2025)
The study aimed to analyze the role of nursing in assisting children and adolescents who are victims of sexual abuse, emphasizing humanized care practices and strategies to mitigate the impact of trauma. This is an integrative literature review, with a search for articles published between 2019 and 2024 in the Virtual Health Library (VHL) and Google Scholar databases. Studies addressing the role of nursing in the care of child and adolescent victims of sexual abuse were included. The analysis of 17 articles highlighted the importance of continuous training of nursing professionals for the early identification of signs of abuse and the provision of sensitive care. The absence of specific protocols represents a challenge, limiting the effectiveness of care. It was evidenced that nursing care is essential to ensure comprehensive and protective assistance for children and adolescents who are victims of sexual abuse. The implementation of specific protocols and participation in interdisciplinary teams strengthen assistance and enable more effective interventions.